Slab1.0: A three-dimensional model of global subduction zone geometries - Hayes, Gavin P.; Wald, David J.; Johnson, Rebecca L. (Journal of Geophysical Research: Solid Earth, 2012)
We describe and present a new model of global subduction zone geometries, called Slab1.0. An extension of previous efforts to constrain the two‐dimensional non‐planar geometry of subduction zones around the focus of large earthquakes, Slab1.0 describes the detailed, non‐planar, three‐dimensional geometry of approximately 85% of subduction zones worldwide. While the model focuses on the detailed form of each slab from their trenches through the seismogenic zone, where it combines data sets from active source and passive seismology, it also continues to the limits of their seismic extent in the upper‐mid mantle, providing a uniform approach to the definition of the entire seismically active slab geometry. Examples are shown for two well‐constrained global locations; models for many other regions are available and can be freely downloaded in several formats from our new Slab1.0 website, http://on.doi.gov/d9ARbS. We describe improvements in our two‐dimensional geometry constraint inversion, including the use of ‘average’ active source seismic data profiles in the shallow trench regions where data are otherwise lacking, derived from the interpolation between other active source seismic data along‐strike in the same subduction zone. We include several analyses of the uncertainty and robustness of our three‐dimensional interpolation methods. In addition, we use the filtered, subduction‐related earthquake data sets compiled to build Slab1.0 in a reassessment of previous analyses of the deep limit of the thrust interface seismogenic zone for all subduction zones included in our global model thus far, concluding that the width of these seismogenic zones is on average 30% larger than previous studies have suggested. Key Points Introduces a new set of detailed 3D global subduction zone models Focuses on the shallow seismogenic zone (unrepresented in previous models) Allows for improved finite‐fault, seismic and tsunami hazard calculations